Upaya Peningkatan Kemampuan Public Speaking Pemuda Sragi Ponorogo: Efforts to Increase Youth Public Speaking Ability in Sragi Ponorogo - Fathoni, Tamrin; Asfahani, Asfahani; Munazatun, Erfa; Setiani, Lilis (LP2M INSURI Ponorogo, 2021)
Everyone is indeed able to speak, but only some are able to mix words into pretty rhetoric and attract the audiences. In communication studies, public speaking skills are part of effective communication, namely conveying messages to the audience in an appropriate way and attracting attention. From the reality in Sragi village of Ponorogo, there are still many youths who are less competent or not confident in speaking in public. Some of these reasons encourage the team to carry out training for public speaking skills. The purpose of this program is to assist the speaking skills of Sragi youth so that they can increase their self-confidence when presenting themselves in public. The ABCD (Asset-Based Community Development) method was employed to conduct the activity, consecutively it was found that innovative and creative training can provide new insights and knowledge about public speaking techniques among each Sragi youth. The result can be derived from this program: first, Sragi youth can do public speaking well and fluently; second, Sragi youth can arrange a certain program properly and correctly according to their needs; and third, Sragi youth have sufficient master of ceremony and public speaking skills. Setiap orang memang dapat berbicara, tetapi hanya beberapa yang mampu mencampurkan kata-kata menjadi retorika yang indah dan menarik perhatian pendengarnya. Dalam ilmu komunikasi, keterampilan berbicara di depan umum merupakan bagian dari komunikasi yang efektif, yaitu menyampaikan pesan kepadak halayak dengan cara yang tepat dan menarik perhatian. Dari kenyataan di Desa Sragi Ponorogo, masih banyak anak muda yang kurang kompeten atau kurang percaya diri dalam berbicara di depan umum. Beberapa alasan tersebut mendorong tim untuk melakukan pelatihan keterampilan berbicara di depan umum. Tujuan dari program ini adalah untuk membantu para remaja Sragi sehingga dapat meningkatkan rasa percaya diri saat tampil di depan umum. Metode ABCD (Asset-Based Community Development) digunakan untuk melaksanakan kegiatan tersebut, sehingga ditemukan bahwa pelatihan yang inovatif dan kreatif dapat memberikan wawasan dan pengetahuan baru tentang teknik public speaking di antara pemuda Sragi. Hasil yang didapat dari program ini adalah: pertama, pemuda Sragi dapat berbicara di depan umum dengan baik dan lancar; kedua, pemuda Sragi dapat menyusun agenda program tertentu dengan baik dan benar sesuai dengan kebutuhannya; dan ketiga, pemuda Sragi memiliki kemampuan MC dan public speaking yang memadai.